Achilles tendinopathy: Exploring injury characteristics and current treatment modalities. (March 2021) - Fares, Mohamad Y.; Khachfe, Hussein H.; Salhab, Hamza A.; Zbib, Jad; Fares, Youssef; Fares, Jawad
Highlights: Achilles tendinopathy is a common overuse injury worldwide. Several biomechanical and anatomical properties govern Achilles tendinopathy. Treatment options vary and include surgical and non-surgical options. Treatment should be customized to the individual case. Further research is required to help assess the viability of current and future therapeutic modalities. Abstract: Achilles tendinopathy is a prevalent overuse injury to the Achilles tendon causing prominent pain and reduction in quality of life. Several biomechanical and anatomical properties govern the pathology of the Achilles tendinopathy, and as a result, choosing the optimal treatment option is challenging. The aim of this review is to study the anatomical and biomechanical characteristics of this injury and explore the available treatment options in order to extrapolate the most suitable option with the best prognosis. Treatment modalities for Achilles tendinopathy vary and include non-operative and operative options. Non-operative treatment modalities include physical therapy, extracorporeal shockwave therapy, injectable agents, and bracing and taping. Operative treatment modalities include surgical procedures, both percutaneous and open. Treatment should be catered to the individual patient. Further research is required in order to confirm the efficacy of the available treatment options, test the viability of novel techniques and approaches, and discover possible new therapeutic modalities.